Evaluation Study: Epidemiological Trends of COVID 19 - Yarmaliza Yarmaliza; Teungku Nih Farisni; Fitriani Fitriani; Fitrah Reynaldi; Zakiyuddin Zakiyuddin; Veni Nella Syahputri; Rinaldy Rinaldy (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
Coronavirus Disease or COVID-19 is still a concern around the world. After additional examination, it was viewed that as a new strain of Covid was the reason. There is still a lot of controversy surrounding this disease, including aspects of diagnosis, treatment, and prevention. Therefore, we conducted a review of studies related to COVID-19 which have been widely published from early 2020 to the end of March 2020. Until now, definitive treatment for COVID-19 has not been found, patients with COVID-19 are only given supportive therapy. The method used in this research is a literature study, which is a study whose research object is in the form of library works, either in the form of scientific journals, books, articles in the mass media, as well as statistical data so as to describe the epidemiological trend of COVID 19. The purpose of writing this article is to knowing the distribution trend of COVID-19, which is still a pandemic issue.